2012
DOI: 10.3892/or.2012.1874
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of silibinin on EGFR signal-induced renal cell carcinoma progression via suppression of the EGFR/MMP-9 signaling pathway

Abstract: Abstract. The activation of epidermal growth factor (EGF) through its receptor, EGFR, is one of the major mechanisms that mediate renal cell carcinoma (RCC) metastasis. Silibinin, a natural flavonoid antioxidant with pleiotropic anticancer capability, has shown anti-metastatic effects in a variety of cancers. However, the mechanism by which silibinin inhibits EGFR signal-induced migration and invasion of RCC cells is not clear. Here, we evaluated the potential roles of EGFR signaling cascade that affects RCC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Liang et al reported the inhibitory effect of silibinin on EGFR signal-induced renal cell carcinoma progression via suppression of the EGFR/MMP-9 signaling pathway [4]. The effect of EGR on renal cell carcinoma was also reported by others [5, 6].…”
Section: Introductionmentioning
confidence: 72%
“…Liang et al reported the inhibitory effect of silibinin on EGFR signal-induced renal cell carcinoma progression via suppression of the EGFR/MMP-9 signaling pathway [4]. The effect of EGR on renal cell carcinoma was also reported by others [5, 6].…”
Section: Introductionmentioning
confidence: 72%
“…Flavonoids, which bind to the ATP-binding site of several kinases, act as RTK inhibitors [39]. Silibinin is a flavonoid and impairs the EGF receptor regulated ERK signaling in various cancer cells [40]. Pre-incubation with silibinin was also reported to affect the early signaling events of the PDGFR activation including ERK and MEK phosphorylation [33].…”
Section: Discussionmentioning
confidence: 99%
“…Результаты исследования клинического значения уровня экспрессии ММП-9 клетками почечноклеточной карциномы в 249 образцах от пациентов и в клеточной линии почечно-клеточного рака человека Caki-2 продемонстрировали статистически значимую корреляцию (р<0,01) между выраженной экспрессией ММП-9 в клинических образцах и неблагоприятным прогнозом (низкой общей выживаемостью). Имеются сообщения об успешной попытке ингибирования транскрипции ММП-9 мРНК с последующим снижением инвазивной способности клеток Caki-2, что позволяет рассматривать ММП-9 как потенциальную мишень противоопухолевой терапии [27,30,32,35,44,53].…”
Section: ммп и их тканевые ингибиторы при раке почкиunclassified